Technical Assistance to Improve the Efficiency and Accuracy of Financial Report Archiving at the Regional Disaster Management Agency - Muhammad Havis; Zaenal Abidin; Kurniawan; Mutawali; Hasnan (Zabags International Journal of Engagement, 2025)
This study aims to enhance the efficiency and accuracy of financial report archiving at the Regional Disaster Management Agency (BPBD) of Tanjung Jabung Timur through a technical assistance program implemented by students from the Sharia Economic Law Study Program at Institut Islam Al-Mujaddid Sabak. Sound archival management of financial documents is critical for accountable public financial governance, particularly in agencies that frequently manage emergency budgets and public aid. Employing a qualitative phenomenological approach, data were collected via participant observation, semi-structured interviews, and document review, and were analyzed thematically with triangulation to ensure credibility. Findings indicate that the technical assistance yielded measurable improvements in archival procedures: a structured classification system was introduced, retrieval times were reduced, and initial steps toward digital archiving were adopted. The intervention also fostered greater staff awareness of public accountability and ethical principles rooted in Islamic economic law, such as amanah (trust) and transparency. The study contributes theoretically by linking archival management and public financial governance in a disaster-response context, and practically by offering a replicable model of university-led technical assistance for strengthening local government archival capacity.